Liturgisk reformarbejde i Danmark: Med fokus på samvirket mellem stat, kirke og folk fra Kirkeordinansen 1537/39 til det 20. århundredes liturgiske revisioner - Enggaard, Nete Helene (Dansk Teologisk Tidsskrift, 2022)
In 2016 the Danish bishops initiated an “historical experiment”, viz. the so-called liturgical debate in the Danish Evangelical Lutheran Church of the years 2017-2021. The aim of the debate was to involve theological scholars, pastors and lay people in the discussion of the liturgical texts that regulate the celebration of the Sunday service and the sacraments. This historical experiment re-opened classical questions regarding the right to initiate liturgical reforms and regulate liturgical rules in the Danish Evangelical Lutheran Church. It also re-opened the question of authority in the Church. This article outlines the most important historical discussions and developments from the Church Ritual (Kirkeritualet) of 1537/39 until the present day in order to shed light on how and by whom liturgical reforms were and still are initiated and executed in Denmark. A special focus is put on the interaction between state, church and people.